2021
DOI: 10.1631/jzus.a2000408
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanical damage diagnosis methodologies based on machine learning and deep learning models

Abstract: A loss of integrity and the effects of damage on mechanical attributes result in macro/micro-mechanical failure, especially in composite structures. As a progressive degradation of material continuity, predictions for any aspects of the initiation and propagation of damage need to be identified by a trustworthy mechanism to guarantee the safety of structures. Besides material design, structural integrity and health need to be monitored carefully. Among the most powerful methods for the detection of damage are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 152 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Recent advances in machine learning in Materials Science and Engineering have provided material scientists with new tools to expedite the collection of microstructure properties. These advancements include deep learning, programming question generation, and automated control and calibration [78][79][80][81][82][83][84][85][86][87]. HPC also continues to expand along with computing offload [88].…”
Section: Future Improvementsmentioning
confidence: 99%
“…Recent advances in machine learning in Materials Science and Engineering have provided material scientists with new tools to expedite the collection of microstructure properties. These advancements include deep learning, programming question generation, and automated control and calibration [78][79][80][81][82][83][84][85][86][87]. HPC also continues to expand along with computing offload [88].…”
Section: Future Improvementsmentioning
confidence: 99%
“…For the future research the comparative analysis with other machine learning methods, e.g., (Asadi et al 2019;Ghalandari et al 2019a;Ghorbani et al 2020c;Joloudari et al 2020;Mosavi et al 2020;Sadeghzadeh et al 2020;Shabani et al 2020;Abdali et al 2021;Mosavi and Safaei-Farouji 2021) would be essential to bring an insight into the true potential of the proposed method. To improve the accuracy and the performance of the proposed method further deep learning, ensemble and hybrid methods for instance, those suggest in (Band et al 2020b;Dehghani et al 2020;Ghorbani et al 2020a;Mosavi et al 2020;Nabipour et al 2020;Mousavi et al 2021;Shamsirband and Mehri Khansari 2021) can come to the consideration.…”
Section: Recommendations For Future Research Workmentioning
confidence: 99%
“…These researchers showed that the mean squared error of the ML prediction of the mechanical properties is several orders of magnitude smaller than the actual value of each attribute, indicating that the model has good training results. Shamsirband and Khansari (2021) believed that the most powerful methods for detecting damage are ML and deep learning. They discussed advanced ML methods and their applications in detecting and predicting material damage.…”
Section: Introductionmentioning
confidence: 99%